Emergency Online Learning in Low-Resource Settings: Effective Student Engagement Strategies - Victoria Abou-Khalil; Samar Helou; Eliane Khalifé; MeiRong Alice Chen; Rwitajit Majumdar; Hiroaki Ogata (MDPI AG, 2021)
We aim to identify the engagement strategies that higher education students, engaging in emergency online learning in low-resource settings, perceive to be effective. We conducted a sequential mixed-methods study based on Moore's interaction framework for distance education. We administered a questionnaire to 313 students engaging in emergency online learning in low-resource settings to examine their perceptions of different engagement strategies. Our results showed that student-content engagement strategies, e.g., screen sharing, summaries, and class recordings, are perceived as the most effective, closely followed by student-teacher strategies, e.g., Q and A sessions and reminders. Student-student strategies, e.g., group chat and collaborative work, are perceived as the least effective. The perceived effectiveness of engagement strategies varies based on the students' gender and technology access. To support instructors, instructional designers, and researchers, we propose a 10-level guide for engaging students during emergency online classes in low-resource settings.